Distinct regulation of hippocampal neuroplasticity and ciliary genes by corticosteroid receptors - Karen R. Mifsud (Nature Portfolio, 2021)
Glucocorticoid hormones (GCs) are of critical importance for maintaining brain health, but their involvement in mental disorders is poorly understood. Here the authors show how GCs act through hippocampal mineralocorticoid and glucocorticoid receptors to impact the gene regulatory programs underpinning neuronal plasticity, ciliogenesis and behavioral adaptation.